Effect of Zilpaterol hydrochloride and steroid implantation on yearling steer feedlot performance, carcass characteristics, and skeletal muscle gene expression - Baxa, Timothy John (Kansas State University, 2008)
Zilpaterol hydrochloride (ZH) is a growth promotant that is approved for use in finishing cattle to improve growth performance and increase lean tissue accumulation. Little is known about the combined effects of ZH with anabolic steroid hormone implants. There is also little published data on the effect these growth promotants have on genes that play a role in skeletal muscle synthesis and degradation. Therefore, two separate studies were conducted to address these issues. The first study evaluated the effects of ZH and the steroid implant Revalor-S (RS) on animal performance and skeletal muscle gene expression in feedlot steers. Four treatments were used to analyze the effects of RS implanted 58 days before ZH, which was fed for 30 days with a 3 day withdrawal. It was determined that ZH and RS additively contribute to improved live and carcass performance; however these compounds had different effects on the abundance of the receptors for ZH as well as the abundance of myosin heavy chain (MHC) mRNA in skeletal muscle of feedlot steers. It was also determined that ZH can cause a transition in the abundance of MHC mRNA isoforms in skeletal muscle that are available for the translation of larger, faster, more glycolytic fiber types of MHC. The second study evaluated the effects of two types of anabolic steroid hormones on myosin heavy chain gene expression. Four treatments were used to measure the effects of trenbolone acetate (TBA) and estradiol (E[subscript]2) on performance and the amount of MHC mRNA in skeletal muscle of finishing steers. It was determined that anabolic steroid implants improve live animal performance, however there was no alteration in the abundance of MHC mRNA in skeletal muscle of feedlot steer for 28 days after implantation; however there was an increase in intermediate fiber type IIA of MHC mRNA in skeletal muscle with increasing days on feed. From these studies we concluded that ZH and anabolic steroids do have an effect on growth performance; however they may differ in the distinct mechanism of action utilized to enhance lean tissue deposition in feedlot steers.
Keywords: Beta-Adrenergic agonist; Cattle; Implant; Myosin; Zilpaterol hydrochloride; Agriculture, Animal Culture and Nutrition (0475)